SALICYLATES ARE ANTI-INFLAMMATORY DRUGS AND THEIR ACTION MECHANISM - Nafisaxon Xasanboyeva Abdullajonovna (Web of Journals Publishing, 2025)
Nonsteroidal anti-inflammatory drugs are aspirin-type or non-narcotic or non-opioid analgesics. In addition, they have anti-inflammatory, antipyretic and uricosuric properties— without addiction liability. They act by inhibiting prostaglandin synthesis. NSAIDs (nonsteroidal anti-inflammatory drugs) can reduce pain, fever and other types of inflammation.
Keywords: Effect, treatment, mechanism, aspirin, inhibitor, chemical, pain.